Use of aqua-chemicals in the hatcheries and fish farms of greater Noakhali, Bangladesh - Hossain, M. Belal; Nurul Amin, Sarker Mohammad; Shamsuddin, M.; Minar, Maruf Hossain (Academic Journals, 2013)
This study was carried out in greater Noakhali region (Lakshmipur, Noakhali and Feni) to evaluate the type of aqua-chemicals used in aquaculture activities where data were collected through questionnaire interview, Focus Group Discussion (FCD), personal contact with fish farmers, hatchery and nursery owner, farm workers. A variety of aqua drugs and chemicals including antibiotics have been using in the region by farmers for fish health management and increasing production. Aqua-chemicals were commonly used for pond preparation, disease control and treatment of the carps, tilapia, prawns and weed fishes. Carps show very positive results when they were treated against the diseases, Motile Aeromonas Septicaemia (MAS), Epizootic Ulcerative Syndrome (EUS), Saprolegniasis, Argulosis, Fin rot, Dropsy, Ichthyophthiriasis with oxytetracycline, potassium permanganate, sumithione, malachite green, dipterex, pillar sulfan, secofon, timsen, geolite and lime. The study also identified the problems associated with the use of chemicals which included lack of knowledge regarding the use of chemicals, appropriate dose, method of application and indiscriminate use of chemicals.